The influence of salt on the gains of steer calves. - Smith, E.F.; Parrish, D.B. (Kansas Agricultural Experiment Station, 2012)
Three lots of steer calves were wintered on silage and 1 pound of soybean pellets per head daily. In addition to this ration Lot 1 received free access to salt. Lot 2 was fed a limited salt allowance (approximately one-sixth of an ounce per head daily) and Lot 2 received no salt.
Keywords: Beef; Salt; Gain; Soybean pellets